The Fall of the Angels - Stuckenbruck, Loren,; Auffarth, Christoph, (Themes in Biblical Narrative ;, 2004)
The fall of the angels is one of the biblical narratives which, above all in the history of the bible's reception, have developed an extraordinary effect: In the biblical canon they appear just as hints (Gen. 6; Isaiah 14; Apocalypse 12). Little concern for the text as well as a tradition and reception not covered by the canon makes the narrative grow and change considerably, as well as freely negotiate in the popular media of iconography, liturgy and theatre. As a completed narrative the fall of the angels appears only in the literature of the apocalyptic movement. The so-called Henoch tradition provides revelations about the cosmos and the secrets of Heaven and Earth. Through this mystery our present world is coded as a battle between good and evil.